Artikel Etika dalam Kehidupan di Negara Demokrasi: . - Wohon, Chandra Christofel (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Ethics is important especially in the life of human behavior. Because of the importance of ethics, ethics should be the main concern of every action and behavior of human subjects. In the life of the state, nation and homeland, it is very important to be based on ethics, because that life will always be related to many people or society. This article will talk about ethics and its importance in the life of a state in a democratic country, such as Indonesia. However, Indonesia as a democracy does not only embrace democracy as it is commonly known, but embraces Pancasila democracy. From that description, the author will then elaborate on how Pancasila democracy is a choice of democracy model in a country, which is full of national ethics